(untitled) (The Review of Diabetic Studies, 2025)
Introduction: Healthcare-associated infections (HAIs) pose a serious risk to patient safety in Intensive Care Units (ICUs). When matching retrospective data from referral hospitals in the Kingdom of Saudi Arabia (KSA), the HAI prevalence rate appears to be persistent; on occasion, upwards of 15.38% HAI, with recurrent and common patterns of catheter-associated urinary tract infections and ventilator-associated pneumonia and with often multidrug-resistant organisms. The nursing workforce is ideally situated to lead this education due to their continuous presence at the bedside, a formalized role identified by the Saudi Arabian Ministry of Health guidelines. Research Objective: The main objective of this systematic review is to consistently analyze the role of nurse-led educational interventions on infection control practices among families of ICU patients in Saudi Arabia hospitals. Research Methods: Using a systematic review approach, we synthesized and collated data from a range of data sources including quantitative studies on behavioral and clinical outcomes, qualitative studies to identify family needs (assurance, proximity), and nurse-reported structural and cultural barriers to attend the needs of family in an ICU setting, and systematic reviews on technology-enabled educational modalities and their effectiveness. Conclusion: Nurses reported the primary barriers were structural (heavy workload: 72.0%, not enough staff: 72.4%), cultural/linguistic (language variability: 64.3%). Consideration of recommendations to improve the barriers include: institutionalizing standardized, consistent, high-quality, bilingual and video-based educational technology; formalizing Advanced nursing roles to engage with family and educate family beforehand; and mandate cultural competence training to establish an easy partnership in a Family-Centred Care approach.